DETERMINATION OF CONSUMER LOYALTY THROUGH CUSTOMER SATISFACTION - Septiano, Renil; Sari, Laynita (Dinasti Publisher, 2020)
Customer satisfaction causes customers to be loyal so that the company can maintain a sustainable competitive advantage. This study aims to determine the impact of brand image, price perception, perceived value on consumer loyalty through customer satisfaction at Rayhan Toko Muslim in the city of Padang. The research method used is associative, with descriptive and verification data disclosure. The population is the consumer of Rayhan Toko Muslim in the city of Padang. Data collection through a survey of 203 respondents. The analysis technique used is path analysis. The results showed that: brand image, perceived price, perceived value, and customer satisfaction had a significant effect on consumer loyalty. All of them have an influence in a positive direction, except for the price perception variable. The management of Rayhan Toko Muslim, pay attention to things that can increase customer loyalty, so that business continuity can be maintained.